The perilous riding behavior and accident of motorcycles in university students - Atmawati, Fera; Nurhalisa, Nurhalisa; Mulyani, Wa Ode Sri; Adyatama Pimpie, Muhammad Reza; Rahman, Walid Wahyudin (Public Health of Indonesia, 2021)
Background: An inevitable traffic accident frequently resulted from the dereliction of individualized community from disobeying regulation which causes an impact on the safety of another person. The impact raised is not merely in terms of material but also non-material.Objective: This research was aimed to know the correlation between risky riding behavior and the accident of motorcycles experienced by university students of Halu Oleo University of Kendari, Indonesia.Methods: This research utilized the cross-sectional design. Data were collected on June 2021 using a validated questionnaire online among 251 respondents. Results: 84.5% of respondents had ever experienced motorcycle accidents. There was a correlation between listening to music while riding (p = 0.973), riding with the speed more than 50 km/hour (p = 0.220), sudden braking (p = 0.267), overtaking without turning rear light (p = 0.518), with the motorcycle accidents.Conclusion: The dangerous riding behavior can potentially decrease the rider's ability and increase the possibility of a car accident. The university could improve safe riding through empowering and encouraging education about riding towards students.